ANALISIS PENERAPAN METODE INDEX CARD MATCH DALAM PEMBIASAAN LITERASI BAHASA PRODUKTIF SISWA SEKOLAH DASAR - Arik Umi Pujiastuti (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
The research carried out aims to describe the results of the productive language literacy of grade 1 primary school students by applying the index card match method and the results of student responses. The type of research used is Classroom Action Research which consists of two cycles. The subjects of this study were students of grade 1 SDN Panyuran 1, Palang District, Tuban Regency. Data collection techniques using test techniques, questionnaires, and documentation. The research instruments used included test sheets, questionnaires. The data analysis technique used is descriptive quantitative.Based on the results of research, the results of productive language skills of students in grade 1 primary school in the first cycle were 67.26% and 87.2% in the second cycle. The results of student’ responses given at the end of the cycle of 98.56% are classically.